Sistemática del pez Petenia splendida (Perciformes: Cichlidae) en el lago Petén Itzá, Guatemala - Méndez, Anaitté (2011)
The Lake Petén Itzá is located in the multiple use zone of the Maya Biosphere Reserve. It belongs to the sub-tropical moist forest (warm) life zone, and has very important flora and fauna diversities. Among the fish spe-cies, the white fish (Petenia splendida) is of high commercial value. The main goal of the present work was to clarify the taxonomic position of the two forms of the white fish in Petén (Guatemala), and to compare it with the Usumacinta (Mexico) form, based on the collected material from 1978 and 2006 (Usumacinta), and collections made during 2008 and 2009 in the Lake Petén Itzá. Samples were obtained from 10 different locations in the lake. From the total of 57 fish specimens collected, 50 fish were selected (25 yellow form and 25 silver form); besides, 21 specimens from 10 locations of the Usumacinta river in Mexico, from the Fish Collection, FCB, UANL. A total of 36 morphometric and 16 meristic characteristics, were analyzed, and also coloration, habitat and fishing method. This study reports the P. splendida of the Lake Petén Itzá with the following characteristics: the yellow form at a depth of 0.5-1.5m with dorsal fin XIv-(Xv)-XvI/11-(12)-13, the silver form at a depth of 2-3m with dorsal fin XIv-(Xv)-XvI/10-(12)-13, and the Usumacinta form with a dorsal fin XIv-(Xv)-Xv/12-(13)-13. The discrimination analysis demonstrates a differentiation among the three analyzed popula-tions. Some of the characteristics are the ocular diameter, the anal source-pelvic source distance and the dorsal source-anal source distance. The geographic area studied has a high diversity of fish fauna along the watershed, and it is possible to observe the anthropogenic damage, due to the overexploitation based the unapplicability of the existent regulation and the urbanization. If this situation continues it could jeopardize the survival of this emblematic specie.